Tumor-platelet interaction in solid tumors - Bürgy, Daniel; Wenz, Frederik; Groden, Christoph; Brockmann, Marc Alexander (International journal of cancer, 2012)
Elevated platelet counts in patients diagnosed with malignant tumors were first described more than 100 years ago. Today it is well known that in many types of solid tumors, thrombocytosis at the time of diagnosis is associated with shorter survival. From this well-documented clinical correlation between platelet count and prognosis of solid tumors, the following questions arise: (i) Are the increased platelet counts the reason for shortened survival as platelet-secreted cytokines might boost tumor growth and angiogenesis? (ii) Do platelets affect tumor metastasis thereby shortening survival time? or (iii) Are increased platelet counts simply an epiphenomenon of tumor growth with larger tumors resulting in higher platelet counts and shorter survival times? We address these three questions within our review of the current literature to provide a comprehensive overview of the current concepts in tumor-platelet interaction.
Gesehen am 03.07.2018